Dilated cardiomyopathy caused by mutation of the PNPLA2 gene: a case report and literature review - Wang, Shuai; Wu, Sha; Peng, Daoquan (Frontiers in Genetics, 2024)
Deficiency of adipose triglyceride lipase (ATGL) due to mutation in PNPLA2 causes neutral lipid storage disease with myopathy (NLSDM), an autosomal recessive disorder (MIM: #610717). NLSDM patients are mainly affected by progressive myopathy, cardiomyopathy, and hepatomegaly. Cardiac involvement was reported in 40%–50% of NLSDM patients. Patients with cardiac involvement have adult-onset progressive heart failure, mimicking dilated or hypertrophic cardiomyopathy. The clinical characteristics, genotype–phenotype correlation, and prognosis of cardiomyopathy secondary to PNPLA2 mutation are not understood. We reported two male patients carrying a homozygous splicing mutation NM_020376.4 (c.757 + 1G>T) in PNPLA2, presenting with severe dilated cardiomyopathy and mild skeletal muscle involvement. Through the literature review, the ECG and imaging features and the prognosis of 49 previously reported cases of cardiomyopathy caused by the PNPLA2 mutation were summarized. This study suggests that NLSDM should be considered a cause of cardiomyopathy, especially in those with elevated creatine kinase (CK) levels, regardless of whether symptoms such as muscle weakness or atrophy are present.